ADAPTIVE FAST RETRANSMISSION WITH RESPECT TO RECEIVER BUFFER (RBUF) SPACE IN SIMULTANEOUS MULTIPATH TRANSMISSION (SMT) - Khan, Samiullah; Qadir, M. Abdul; Ali Khan, Fawad (Malaysian Journal of Computer Science, 2018)
imultaneous Multipath Transmission has inherited problem of out-of-order packet reception. This causes receiver buffer (Rbuf) blocking, which degrades the aggregated throughput and restricts the efficiency of fastest path to its slowest companion path. This research proposed SMT-Adaptive Fast Retransmit mechanism that uses fast retransmission threshold, adapts to the size of Rbuf in order to encounter Rbuf blocking problem. In bandwidth and packet loss based disparity scenarios, SMT-AFR achieved the highest aggregated throughput and remained unaffected with respect to various Rbuf sizes. In delay based disparity scenarios, the performance of SMT-AFR affected with a decrease in Rbuf size. Simulation results revealed that SMT-AFR has solved the Rbuf blocking problem in bandwidth and packet loss disparity scenarios. There is a need for the multipath disparity aware scheduler to improve SMT-AFR performance in delay based disparity.